Swimming Impedes Intestinal Microbiota and Lipid Metabolites of Tumorigenesis in Colitis-Associated Cancer - Wang, Weiyi; Xu, Ying; Wang, Xiaofeng; Chu, Yimin; Zhang, Haiqin; Zhou, Lu; Zhu, Haijin; Li, Ji; Kuai, Rong; Zhou, Fengli; Yang, Daming; Peng, Haixia (Frontiers in Oncology, 2022)
Background: Accumulating data support that regular physical activity potentially inhibits chronic colitis, a risk factor for colitis-associated cancer (CAC). However, possible effects of physical activity on CAC and the underlying mechanisms remain poorly understood. Methods: A pretreatment of swimming on azoxymethane/dextran sodium sulfate (AOM/DSS)-induced CAC mice was implemented to determine its protective effect. Inflammation and tumorigenesis were assessed using colorectums from C57BL/6 mice. In order to determine how swimming alters colonic lipid metabolism and gene expression, a comparative analysis was conducted. Meanwhile, alterations in intestinal microbiota and short-chain fatty acids (SCFAs) were detected and analyzed. Finally, integration analysis of colonic lipid metabolism with gene expression and intestinal microbiota was performed respectively. Result: Swimming pretreatment relieved bowel inflammation and minimize tumor formation. We demonstrated that Prostaglandin E2 (PGE2)/ PGE2 receptor 2 subtype (EP2) signaling as a potential regulatory target for swimming induces colonic lipid metabolites. Swimming-induced genera, Erysipelatoclostridium, Parabacteroides, Bacteroides, Rikenellaceae_RC9_gut_group, induced intestinal SCFAs and affected the function of colonic lipid metabolites enriched in Glycerophospholipid metabolism and Choline metabolism in cancer. . Conclusion: According to our experiments, swimming pretreatment can protect mice from CAC by intervention in the possible link between colonic lipid metabolites and PGE2/EP2 signaling. Further, swimming induced genera and probiotics promoted Glycerophospholipid metabolism and Choline metabolism in cancer, the major constituent of colonic lipid metabolites, and increased SCFAs, which were also important mechanism for the anti-inflammatory and anti-tumorigenic effects of swimming.